The impact of the cyber-attack on Estonia in 2007 on the development of cybersecurity policies - Bozhinov, Zharko (Z. Bozhinov, 2024)
This master's thesis explores the impact of the 2007 cyberattack on Estonia, as well as how it affected cybersecurity policies in several EU member states and Estonia itself. Taking on a realistic approach, the thesis examines the key players and elements of the attack, revealing the complex ways in which it altered Estonia's cybersecurity environment. The three top EU cybersecurity countries—France, Lithuania, and Spain—as determined by the Global Cybersecurity Index (GCI) are also the subjects of the research. The study uses a qualitative research methodology and places a strong emphasis on analysis of primary and secondary data sources, case studies, and comparison techniques. These sources include academic studies, government documents, and perceptive expert interviews. Data triangulation enhances the reliability of the results. This research aims to provide a thorough understanding of how the cyberattack led unique development in policies across these countries by using a comparative lens. According to findings, Estonia responded to the cyber threat with rapid legislative changes that demonstrated a pro-active attitude to cybersecurity. Comparative analysis also reveals unique national details in policy responses, such as France's emphasis on setting the standard for respecting cyber risk assessments and Lithuania's and Spain's emphasis on excellent coordination of the governments' cybersecurity-related agencies. These conclusions provide insight into the adaptive measures that each country has taken. Magistrsko delo obravnava vpliv kibernetskega napada iz leta 2007 na Estonijo ter njegov vpliv na politike kibernetske varnosti v več državah članicah EU in v Estoniji sami. Z realističnim pristopom magistrsko delo obravnava ključne akterje in elemente napada ter razkriva zapletene načine, na katere je spremenil estonsko okolje kibernetske varnosti. Predmet raziskave so tudi tri najboljše države EU na področju kibernetske varnosti - Francija, Litva in Španija - kot jih določa globalni indeks kibernetske ...